Hybrid AC and DC power distribution - S. Jayawardena (Ceylon Journal of Science, 2017)
Interest in the use of DC for medium and low voltage distribution circuits is growing as a means of reducing the multiple power conversion stages associated with connecting renewable energy sources and DC powered consumer electronic devices to the existing AC system.   The possibility of carrying AC power and injected DC power at the distribution transformer in the same distribution line and filtering out them separately to AC and DC loads were investigated. Both simulations and laboratory experiments were used to prove this concept of hybrid distribution. A comparative study was carried out to show that the proposed hybrid solution minimises the energy losses in power conversion stages when integrating renewables.